Parallel Space-Time Adaptive Processing On a Cluster of Personal Computers - Silva, Fernando; Lamont, Gary B. (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD), 1999)
This work evaluates the capabilities and the performance of the Air Force Institute of Technology's Pile-of-PCs for parallel digital signal processing using space-time adaptive processing (STAP) under the Linux OS. The MITRE RT_STAP Benchmark version 1.1 is ported and executed on it, as well as on a cluster of six Sun SPARC workstations connected by a Myrinet network (the AFIT NOW), and on a IBM SP for comparison. Modifications to the RT_STAP benchmark source code are performed to accommodate the BLAS routines obtained from the US Department of Energy's Accelerated Strategic Computing Initiative, and the FFTPACK from the Netlib repository, allowing improvements in the sustained Gflops/sec rales. However, the Pile-of-PCs also reveals limited scalability as a result of severe communication overheads imposed by RT ST AP cornerturn operations. Analysis of experimental data indicates that the PC Cluster outperforms AFIT NOW but needs interconnection network improvements to be globally competitive to multicomputers such as the IBM SP.